Artificial Intelligence in Accounting: A Qualitative Research - Marek CIESLAK; PhD (Communications of International Proceedings, 2024)
The motive behind this study is to explore the transformative impact of Artificial Intelligence (AI) on the accounting profession and its processes. Despite the significant advancements in AI, there exists a void in the literature regarding a comprehensive analysis of AI's benefits, challenges, and future implications in accounting. This study addresses this gap by examining the evolution and integration of AI in accounting tasks. Methodologically, the study employs a qualitative approach, analyzing existing literature, case studies, and industry reports to assess AI's role in automating routine tasks, enhancing accuracy, and providing valuable insights for decision-making. The paper also reviews historical developments in the use of computers and computer systems in accounting prior to AI. The findings reveal that AI significantly improves efficiency and accuracy in accounting by automating data entry, invoice processing, and reconciliation. AI-powered tools excel in predictive analytics and fraud detection, providing deeper insights and enhancing decision-making capabilities. However, challenges such as data privacy, security concerns, and high implementation costs persist. The future of AI in accounting is promising, with potential developments in advanced analytics, blockchain integration, and AI-driven advisory services poised to revolutionize the field. This comprehensive analysis underscores the importance of understanding AI’s impact on accounting to navigate its implementation effectively.
Keywords: Artificial Intelligence (AI); Accounting Automation; Computerized Accounting; Future of Accounting